Ambulatory care provided by office-based specialists in the United States. - Valderas, J; Starfield, B; Forrest, C; Sibbald, B; Roland, M (2009)
PURPOSE: Increasing use of specialist services in the United States is leading to a perception of a specialist shortage. Little is known, however, about the nature of care provided by this secondary level of services. The aim of this study was to examine the content of care provided by specialists in community settings, including visits for which the patient had been referred by another physician. METHODS: Nationally representative visit data were obtained from the National Ambulatory Medical Care Survey (NAMCS) for the years 2002 through 2004. To describe the nature of care, we developed a taxonomy of office-based visit types and constructed logistic regression models allowing for adjusted comparisons of specialty types. RESULTS: Overall, 46.3% of visits were for routine follow-up and preventive care of patients already known to the specialist. Referrals accounted for only 30.4% of all visits. Specialists were more likely to report sharing care with other physicians for referred, compared with not referred, patients (odds ratio [OR] = 2.99; 95% confidence interval [CI], 2.52-3.55). Overall, 73.6% of all visits resulted in a return appointment with the same physician, in more than one-half of all cases as a result of a routine or preventive care visit. CONCLUSIONS: Ambulatory office-based activity of specialists includes a large share of routine and preventive care for patients already known, not referred, to the physician. It is likely that many of these services could be managed in primary care settings, lessening demand for specialists and improving coordination of care.